50 Años de Sánscrito en la Universidad de Costa Rica - Morales Harley, Roberto (2019)
In 1968, professor emeritus and Costa Rican humanist Hilda Chen-Apuy Espinoza, who had received a UNESCO scholarship to study Asian cultures and to strengthen the East-West bond, inaugurates Sanskrit studies at the University of Costa Rica. This paper seeks to review the story of Sanskrit and Indian studies in Costa Rica, to contextualize the teaching of this Indo-European classical language at the University of Costa Rica, and to defend both its relevance in the Hispanic world and its validity for modern society. The conclusions point out the pertinency of including Sanskrit in the Department of Classical Philology, in ways such as promoting language learning, strengthening grammatical knowledge, studying ancient civilizations, valorizing contemporary groups, preserving cultural productions, defending human patrimony, and offering meeting points between past and present, between East and West, between India and Costa Rica.